2019
DOI: 10.1177/1753425919842932
|View full text |Cite
|
Sign up to set email alerts
|

Serum miR-21 expression correlates with radiographic progression but also low bone mineral density in patients with ankylosing spondylitis: a cross-sectional study

Abstract: Increased expressions of miR-21 have been detected in ankylosing spondylitis (AS) patients. The current study was performed to examine the serum miR-21 expression with radiographic severity in AS patients, which was determined based on the modified New York (NY) criteria for sacroiliac joints assessment and modified Stoke Ankylosing Spondylitis Spinal Score (mSASSS) system for spine involvement. Bone mineral density at lumbar 1–4 and femoral neck were examined by dual-energy absorptiometry (DXA). Serum miR-21 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 34 publications
2
8
0
2
Order By: Relevance
“… 16 In the present study, lnc‐GAS5 expression was found to be elevated, while the expression of its targets, miR‐21 and miR‐140, was decreased in AR patients compared to controls, which is partly in line with previous studies. 9 , 15 , 16 Furthermore, lnc‐GAS5 expression was negatively associated with miR‐21 and miR‐140 expression. There are some potential explanations for these findings.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“… 16 In the present study, lnc‐GAS5 expression was found to be elevated, while the expression of its targets, miR‐21 and miR‐140, was decreased in AR patients compared to controls, which is partly in line with previous studies. 9 , 15 , 16 Furthermore, lnc‐GAS5 expression was negatively associated with miR‐21 and miR‐140 expression. There are some potential explanations for these findings.…”
Section: Discussionsupporting
confidence: 92%
“…Meanwhile, miR‐140 expression is downregulated in synovial fibrous tissues in RA 15 . Furthermore, upregulated miR‐21 expression has been detected in patients with ankylosing spondylitis (AS) compared to healthy controls 16 . In the present study, lnc‐GAS5 expression was found to be elevated, while the expression of its targets, miR‐21 and miR‐140, was decreased in AR patients compared to controls, which is partly in line with previous studies 9,15,16 .…”
Section: Discussionsupporting
confidence: 91%
“…19 Our research group has previously discovered a positive relationship between expressions of serum miR-21 and lower bone mineral density as well as radiographic progression in patients with AS. 20 Taken together, we hypothesize that miR-21 functions as the mediator between inflammation and abnormal bone formation. Thus, this series of investigations are carried out to explore whether miR-21 contributes to new bone formation mediated by TNF-a.…”
Section: Introductionmentioning
confidence: 81%
“…19 Our research group has previously discovered a positive relationship between expressions of serum miR-21 and lower bone mineral density as well as radiographic progression in patients with AS. 20…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Huang et al reported greater miR-21 expression in whole blood of patients with AS compared to controls [ 91 ]. Recently, Zou et al showed that upregulation of miR-21 was associated with radiographic severity of AS [ 92 ]. The studies regarding RA reported decreased miR-21 level in PBMCs, CD4+ T cells [ 93 ], and plasma [ 94 ].…”
Section: Discussionmentioning
confidence: 99%